Age-related differences in postural control: effects of the complexity of visual manipulation and sensorimotor contribution to postural performance - Toledo, Diana R.; Barela, Jose A. [UNESP] (Springer, 2014)
Patterns of adaptive changes to the exposure to a sinusoidal visual stimulus can be influenced by stimulus characteristics as well as the integrity of the sensory and motor systems involved in the task. Sensorimotor deficits due to aging might alter postural responses to visual manipulation, especially in more demanding tasks. The purpose of this study was to compare postural control between young and older adults at different levels of complexity and to examine whether possible sensory and/or motor changes account for postural performance differences in older adults. Older and young adults were submitted to the following tests: postural control assessments, i.e., body sway during upright stance and induced by movement of a visual scene (moving room paradigm); sensory assessments, i.e., visual (acuity and contrast sensitivity) and somatosensory (tactile foot sensitivity and detection of passive ankle motion); and motor assessments, i.e., isometric ankle torque and muscular activity latency after stance perturbation. Older adults had worse sensory and motor performance, larger body sway amplitude during stance and stronger coupling between body sway and moving room motion than younger adults. Multiple linear regression analyses indicated that the threshold for the detection of passive ankle motion contributed the most to variances in body sway and this contribution was more striking when visual information was manipulated in a more unpredictable way. The present study suggests that less accurate information about body position is more detrimental to controlling body position, mainly for older adults in more demanding tasks.
Keywords: Posture; Sensorimotor system; Aging; Moving room